(untitled) (The Review of Diabetic Studies, 2023)
This article reviews the relationship between dyslipidemia, chronic kidney disease, and cardiovascular diseases in patients with diabetes. Diabetes mellitus is associated with complications in the cardiovascular and renal system, and is increasing in prevalence worldwide. Modification of the multifactorial risk factors, in particular dyslipidemia, has been suggested to reduce the rates of diabetes-related complications. Dyslipidemia in diabetes is a condition that includes hypertriglyceridemia, low high-density lipoprotein levels, and increased small and dense low-density lipoprotein particles. This condition is associated with higher cardiovascular risk and mortality in diabetic patients. Current treatment guidelines focus on lowering the low-density lipoprotein cholesterol level; multiple trials have confirmed the cardiovascular benefits of treatment with statins. Chronic kidney disease also contributes to dyslipidemia, and dyslipidemia in turn is related to the occurrence and progression of diabetic nephropathy. Different patterns of dyslipidemia are associated with different stages of diabetic nephropathy. Some trials have shown that treatment with statins not only decreased the risk of cardiovascular events, but also delayed the progression of diabetic nephropathy. However, studies using statins as the sole treatment of hyperlipidemia in patients on dialysis have not shown benefits with respect to cardiovascular risk. Diabetic patients with nephropathy have a higher risk of cardiovascular events than those without nephropathy. The degree of albuminuria and the reduction in estimated glomerular filtration rate are also correlated with the risk of cardiovascular events. Treatment with angiotensinconverting enzyme inhibitors and angiotensin II receptor blockers to reduce albuminuria in diabetic patients has been shown to decrease the risk of cardiovascular morbidity and mortality.